CD8 Effector T Cells Function Synergistically With Broadly Neutralizing Antibodies to Enhance Suppression of HIV Infection - Veenhuis, Rebecca T.; Garliss, Caroline C.; Bailey, Justin R.; Blankson, Joel N. (Frontiers in Immunology, 2021)
HIV-specific CD8 T cells and broadly neutralizing antibodies (bNAbs) both contribute to the control of viremia, but in most cases, neither can completely suppress viral replication. To date, therapeutic vaccines have not been successful in eliciting HIV-specific CD8 T cell or bNAb responses that are capable of preventing long-term viral rebound upon ART cessation. These challenges suggest that a combinatorial approach that harnesses both bNAbs and CD8 T cell responses may be necessary for long term control of viral replication. In this study we demonstrate a synergistic interaction between CD8 T cells and bNAbs using an in vitro model. Our data suggest that this combinatorial approach is very effective at suppressing viral replication in vitro and should be considered in future therapeutic studies.